PRIVATE LABEL : KAJIAN PERSEPSI KONSUMEN AKAN KUALITAS DAN VALUE FOR MONEY - Natanael Christian Allegro (Universitas Trunojoyo Madura, 2015)
The current modern retail business has grown rapidly and it’s very competitive with each other. One of the means used to compete is to create a private label. With their private label, modern retail can sell their products at cheaper price than the national brand products. But consumers have different perceptions about private label products. Consumer perceptionis based on the price and quality of products.This article discusses about consumer perceptions of the quality and value for money for private label products. The conclusion of this discussion is to determine how perceptions of private label consumer products based on product’s quality and value for money.This discussion is necessary because at this time many different perceptions o fprivate label products and the necessary discussion about consumer perception study to find a clear consumer perceptions towards private label products.